Water cycle algorithm-based PID controller for AVR. Issue 3 (16th April 2020) - Pachauri, Nikhil
Abstract : Purpose: In a power system, the purpose of automatic voltage regulator (AVR) is the voltage control of synchronous generator. Power system stability and security depends on the AVR. Design/methodology/approach: The present work is concentrated on the precise terminal voltage control of AVR system and simultaneously maintaining the stability of the system. Therefore, an optimal proportional–integral–derivative (PID) controller is proposed. An optimization technique inspired from Mother Nature, i.e. water cycle algorithm (WCA) is used to evaluate the optimum parameter values of PID controller leading to WCA-tuned PID (WCA-PID). The performance of WCA-PID is compared with other controller reported in the literature. Findings: Simulation results show that WCA-PID regulates the terminal voltage more preciously and accurately in comparison to other controller. Further, it is more robust toward parametric uncertainty, set-point tracking and disturbance rejection in comparison to other controller reported in the literature. Originality/value: The work is not published anywhere else.